Mixed Germ Cell Tumor of Testis with Isolated Scapular Metastasis: A Case Report and Review of the Literature - Dipti Rani Samanta; Chaitali Bose; Roopesh Krishnappa; Saumyaranjan Mishra; Sulagna Mohanty; Ashish Upadhyay; Surendra Nath Senapati (Case Reports in Urology)
Bone metastasis is a rare entity in germ cell tumor of testis and is a poor prognostic site. It is usually associated with synchronous metastasis at other sites. Till now very few cases of isolated bone metastasis of germ cell tumor of testis have been reported but none have reported scapular metastasis. We are reporting a case of nonseminomatous germ cell tumor of right testis that was operated eight months ago and now presented with isolated scapular metastasis. Histopathology of the scapular tissue revealed rhabdomyosarcoma or poorly differentiated synovial sarcoma. Immunohistochemistry with serum markers concluded it to be metastatic germ cell tumor. To the best of our knowledge this is the first reported case of scapular metastasis of testicular germ cell tumor. This case is being reported here due to dilemmatic way of presentation and also to emphasize that histopathology may sometimes misguide and immunohistochemistry is necessary in such cases.